Quizizz And Hardwork Character in Geometry Online Lecture: How It Influence? - Munfarikhatin, Anis; Pagiling, Sadrack Luden; Mayasari, Dian; Natsir, Irmawaty (Journal of Education Reseach and Evaluation, 2021)
The Quizizz online quiz application and the application of hard work characters have an impact on student achievement, especially on geometry courses. This study aims to investigate the influence the Quizizz online quiz and the character of student hard work on student achievement in online geometry lectures. This study involved all semester 2 and 4 students majoring in mathematics education as a research sample. The instrument used was in the form of a quizizz online quiz learning questionnaire and hard work characters. The proper questionnaire is used as an instrument for collecting data through online media. The questionnaire scale used the Likert scale with the criteria of strongly agree, agree, half agree, disagree, strongly disagree. This research is a quantitative research with ex post facto research design. Student achievement data is obtained from the average cognitive value of students during their online lectures with quizizz. Initial data analysis uses normality test, classic assumption test and influence test. The results showed that the influence of quizizz on student achievement by 69%, the effect of hard work character on learning achievement by 46%, and simultaneously quizizz online quiz and hard work character can influence student learning achievement by 68%. The contribution of this study is that the application of online quiz Quizizz and the character of hard work in online learning, especially geometry, has a dominant influence on student achievement so lecturers can apply to improve the students’ achievement.